Nurses' knowledge and understanding of obstacles encountered them when administering resuscitation medications: a cross-sectional study from Palestine - Rawan I. Qedan; Marah A. Daibes; Samah W. Al-Jabi; Amer A. Koni; Sa'ed H. Zyoud (BMC, 2022)
Abstract Background Medication errors (ME) are one of the most important reasons for patient morbidity and mortality, but insufficient drug knowledge among nurses is considered a major factor in drug administration errors. Furthermore, the complex and stressful systems surrounding resuscitation events increase nursing errors. Aims This study aimed to assess the knowledge about resuscitation medications and understand the obstacles faced by nurses when giving resuscitation medications. Additionally, errors in the reporting of resuscitation medication administration and the reasons that prevented nurses from reporting errors were investigated. Methods A cross-sectional study was conducted in the West Bank, Palestine. Convenient sampling was used to collect data, which was collected via a face-to-face interview questionnaire taken from a previous study. The questionnaire consisted of five parts: demographic data, knowledge of resuscitation medications (20 true/false questions), self-evaluation and causes behind not reporting ME, with suggestions to decrease ME. Results A total of 200 nurses participated in the study. Nurses were found to have insufficient knowledge about resuscitation medications (58.6%). A high knowledge score was associated with male nurses, those working in the general ward, the cardiac care unit (CCU), the intensive care unit (ICU) and the general ward. The main obstacles nurses faced when administering resuscitation medication were the chaotic environment in cardiopulmonary resuscitation (62%), the unavailability of pharmacists for a whole day (61%), and different medications that look alike in the packaging (61%). Most nurses (70.5%) hoped to gain additional training. In our study, we found no compatibility in the definition of ME between nurses and hospitals (43.5%). Conclusions Nurses had insufficient knowledge of resuscitation medications. One of the obstacles nurses faced was that pharmacists should appropriately arrange medications, and nurses wanted continuous learning and additional training about resuscitation medications to decrease ME.